A Comprehensive Analysis of Remittances and Basic Level Government School Enrollment in Nepal - Acharya, Bisna; Poudel, Omkar; Upadhyaya, Yadav Mani; Acharya, Pradeep (International Research Journal of MMC, 2024)
This study aims to examine the factors that impact student enrollment in government schools at the basic level in Nepal. The data were collected from secondary sources publication over the periods of 2000-2022. The Autoregressive Distributed Lag (ARDL) model was applied to analyze the correlations between enrollment and economic factors, such as per capita GDP, population growth, and remittances, in both the short-term and long-term. The results suggest that remittances have a significant negative impact on enrollment, raising concerns about the absence of parents due to working abroad. On the other hand, the level of per capita GDP had a positive effect on the accessibility of education, highlighting the importance of economic development. The population growth did not have a significant impact in this model. The co-integration test suggests a strong and lasting connection between the variables, while the Granger causality tests reveal that remittances and per capita GDP had a significant impact on enrollment. These findings offer valuable insights for policymakers aiming to improve access to high-quality education for every child in Nepal. The paper also discussed potential areas for future research, such as investigating the underlying causes of the negative impacts of remittances and addressing the issue of serial correlation in the model.